Genome-wide association for mapping QTLs linked to protein and oil contents in soybean - Dias, Douglas Anônio; Polo, Leandra Regina Texeira; Lazarri, Fabiane; da Silva, Glacy Jaqueline; Schuster, Ivan (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to identify single-nucleotide polymorphism (SNP) markers linked with quantitative trait loci (QTLs) associated with increased contents of protein and oil in soybean. A total of 169 Brazilian soybean varieties, genotyped with 6,000 SNP markers, were evaluated. Protein and oil contents were obtained with the near-infrared reflectance method. Correlation and multiple linear regression analyses were used to identify linkage disequilibrium between SNP markers and the QTLs associated with the two characteristics. Seven QTLs were found to be associated with protein content, on six chromosomes (2, 6, 11, 12, 13, and 16), explaining 60.9% of the variation in this trait. For oil content, eight QTLs were identified on six chromosomes (1, 4, 5, 6, 17, and 19), explaining 78.3% of the variation in the trait. The correlation between the number of loci containing favorable alleles and the evaluated characteristics was 0.49 for protein content and 0.60 for oil content. The molecular markers identified are mapped in genomic regions containing QTLs previously mapped for both characteristics, which reinforces the association between these regions and the genetic control of oil and protein contents in soybean.